Periarterial divestment in pancreatic cancer surgery - Diener, Markus K.; Mihaljevic, André Leopold; Strobel, Oliver; Loos, Martin; Schmidt, Thomas; Schneider, Martin; Berchtold, Christoph; Mehrabi, Arianeb; Müller, Beat P.; Jiang, Kuirong; Neoptolemos, John P.; Hackert, Thilo; et al. (Surgery, 2021)
Background - Modern pancreatic cancer surgery changed with the introduction of effective neoadjuvant therapies. Complete tumor resection is the mainstay for long-term, disease-free, and overall survival and has been a prerequisite for decreasing local recurrence. The medial resection margin in the area of the superior mesenteric vessels limits the radicalness of the resection, especially in borderline and locally advanced cases. Therefore, the periarterial soft tissue around the peripancreatic visceral arteries must be completely cleared. This procedure, namely periarterial divestment, is technically demanding but often represents an alternative to arterial resection. - Objective - Here we describe the technique and our initial experience with periarterial divestment along the peripancreatic visceral arteries during pancreatic surgery. This technique, in combination with previously published resection strategies, such as artery first maneuver and mesenterico-portal venous bypass first, enables tumor resection in locally advanced pancreatic cancer. - Conclusion - Periarterial divestment can prevent the need for arterial resection in borderline and locally advanced pancreatic cancer, especially after neoadjuvant therapy. The feasibility, improved safety, and oncologic equivalence of arterial divestment versus arterial resection for pancreatic cancer surgery must be evaluated by clinical trials.